Vortex duration in the pulmonary artery does not depend on vascular Afterload: a sign of adaptation? - Sabry, Malak; Wieslander, Björn; Hermida, Uxio; Fernandes, Joao Filipe; Keramati, Hamed; Ugander, Martin; Abdula, Goran; Yacoub, Magdi H.; Lamata, Pablo; Marlevi, David; De Vecchi, Adelaide (Computers in biology and medicine, 2025)
Pulmonary Hypertension (PH) is a serious condition defined by a mean Pulmonary Arterial Pressure (mPAP) greater than 20 mmHg. Using 4D Flow MRI, a strong empirical correlation has been observed between the duration of a blood vortex in the Main Pulmonary Artery (MPA) and mPAP. The mechanisms underlying this relationship and their implications on disease management, however, remain unknown. – Digital Twins of blood flow based on Computational Fluid Dynamic (CFD) models were calibrated based on routine MRI data from 25 subjects with suspected PH. In each case, the duration of the pulmonary vortex was computed, using both 4D Flow MRI data directly and the corresponding in-silico model. The models were then used to perform a parametric study to investigate the effect on vortex duration of mechanistic factors, such as arterial anatomical remodeling, right ventricle (RV) ejection and afterload. – Both digital twins and 4D Flow MRI data reproduced the empirical relationship between vortex duration and mPAP (R2 > 0.9, p < 0.001). CFD simulations revealed that changes in afterload had surprisingly a negligible effect on the vortex duration (1 % change in standard deviation, per one afterload standard deviation change) despite causing more than 80 % of the mPAP variations. On the contrary, the vessel remodeling and RV ejection characteristics, both pertaining to the response to the hypertensive burden, caused in the simulations the most significant changes in vortex duration (∼60 % for shape, and 17–77 % for RV ejection). – An in-silico approach was able to infer mPAP in a range of control and PH subjects by recapitulating its empirical relationship with vortex duration. Parametric analysis showed that vortex duration is a signature of the RV-PA system adaptation to the burden of PH rather than a direct result of acute afterload changes. This finding could potentially impact patient management once validated in clinical trials. [Display omitted] •Digital twins reproduced the relation between vortex duration and pressure (mPAP).•In-silico, vortex duration is not a direct consequence of afterload changes, but a signature of adaptation to PH burden.•Computer simulations of hemodynamics in the pulmonary arteries have the potential to guide healthcare interventions.